Regulating Competition and Cartelisation in the Corporate Real Estate Sector: The Emerging Market Case - Amit Kumar Kashyap; Pranav Singh Rathore; Kadambari Tripathi (Otoritas : Jurnal Ilmu Pemerintahan, 2021)
The main reason for an increase in cartelisation can be attributed to the liberalisation of the economy in India resulting in de-regulation and empowering the enterprises to be at the helm of their affairs. Cartelisation as per UNCTAD impedes healthy competition by fixing prices and restricting supply. The paper gains significance as India aspires to provide housing to all by 2022 but the COVID-19 pandemic coupled with the issue of cartelisation has worsened the situation. The boom in the Corporate Real Estate sector has been coupled with an increase in the anti-competitive practices prevailing in this sector and has negatively impacted the economy. The paper has analysed the provisions in the Indian legal regime as well the legal regimes of the USA and UK regarding cartelization. The Indian regime falls short on various counts when compared with the law of developed nations like the USA and UK, which must be tackled on a war footing. The sector has the potential of opening up numerous opportunities including providing jobs to the Indian youth. The paper aims at providing relevant suggestions in that regard, including the need for whistleblower protection and to have a Cement Regulatory Authority among other things that might prove helpful for the legislators aiming to attract 100 lakh crores in the infrastructure sector in the next five years.